Caesarean delivery on maternal request (CDMR): clinical and ethical dilemma - Mann, Ankita; Mehta, Sumita; Grover, Anshul (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Now a days, in developing countries like India, one of the most common contributing factor for increasing caesarean section rate is CDMR (Caesarean delivery on maternal request). Incidence of CDMR reached upto 18 percent of total caesarean deliveries worldwide. The issue of CDMR is ongoing bioethical debate which highlights the struggle to balance patient autonomy with duty of obstetrician to uphold the principle of beneficence, non maleficence and justice. Our mission should be to promote safe, effective and satisfying maternity care for all women and their families through research, education, expertise and advocacy.